Unveiling physiological changes in pregnancy: Integrative Study focusing on nursing consultation (Research, Society and Development, 2020)
Objective: To identify the physiological changes that occur in women during the gestational process. Method: This is an Integrative Literature Review (RIL), whose function is to perform a synthesis of knowledge from previous studies. The search was of the paired type through the use of Health Sciences Descriptors (DECS), Gestation, Prenatal and Modifications. Results: Changes in the cardiovascular, hematological, respiratory, gastro-intestinal tract, integumentary, urinary, musculoskeletal systems, nervous, endocrine and genital. Discussion: These changes arise with the purpose of adapting the maternal organism to the new life generated and, sometimes, bring great discomfort and concerns for pregnant women - mainly - in the case of primiparous women, with a biopsychosocial impact on the life of these pregnant women. Conclusion: Therefore, it is up to the health professional to be aware of the limit between physiology and pathology related to pregnancy, as well as being able to guide and intervene in practices that alleviate the effects of the changes and reduce the anxiety generated by these changes.